2013
DOI: 10.1016/j.chemgeo.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sulphur on the structure of silicate melts under oxidizing conditions

Abstract: International audienceIn magmatic systems, sulphur is an important volatile element after C, H and O. Under oxidizing conditions, S dissolves in aluminosilicate melt as sulphate groups (SO42 −). The way SO42 − groups dissolve in the melt is currently poorly understood. We present experimental results of the effect of SO42 − dissolution on the aluminosilicate melt structure. Glasses of haplogranitic (HPG) and anorthite-diopside eutectic (An-Di) compositions were synthesized at 300 MPa and 1250 °C and under oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 120 publications
(155 reference statements)
2
21
0
Order By: Relevance
“…The acquired 29 Si Direct MAS spectrum exhibits a slight peak asymmetry witnessing that the 29 Si spectrum is a complex convolution of individual peaks; each of these being attributed to a given Q n species (e.g. Lippmaa et al, 1980;Grimmer et al, 1984;Schramm et al, 1984;Maekawa et al, 1991;Stebbins, 1995;Zhang et al, 1997;Schmidt et al, 2000;Schneider et al, 2003;Mysen and Cody, 2005;Malfait et al, 2007b;Angeli et al, 2011;Davis et al, 2011;Morizet et al, 2013b). The evidence for several Q n species is further asserted by the various NMR experiments we have conducted.…”
Section: Si Mas Nmrmentioning
confidence: 52%
See 1 more Smart Citation
“…The acquired 29 Si Direct MAS spectrum exhibits a slight peak asymmetry witnessing that the 29 Si spectrum is a complex convolution of individual peaks; each of these being attributed to a given Q n species (e.g. Lippmaa et al, 1980;Grimmer et al, 1984;Schramm et al, 1984;Maekawa et al, 1991;Stebbins, 1995;Zhang et al, 1997;Schmidt et al, 2000;Schneider et al, 2003;Mysen and Cody, 2005;Malfait et al, 2007b;Angeli et al, 2011;Davis et al, 2011;Morizet et al, 2013b). The evidence for several Q n species is further asserted by the various NMR experiments we have conducted.…”
Section: Si Mas Nmrmentioning
confidence: 52%
“…The 29 Si NMR spectrum deconvolution procedure has been reported in previous work (Morizet et al, 2013b(Morizet et al, , 2014b; and references therein). The 29 Si NMR spectrum deconvolution was conducted simultaneously on the entire set of spectra and using three Gaussian peaks.…”
Section: Si Mas Nmrmentioning
confidence: 98%
“…Many papers have quantified the uptake of water, CO 2 , and sulfur in silicate glasses and magmas and have noted their importance to magmatic and volcanic processes. 30,31,[35][36][37][38][39][40][41][42][43][44] Because the uptake of CO 2 is reasonably well documented, we consider qualitatively the reaction of CO 2 with oxygen species in melts. The early studies of Eggler and Rosenhauer 86 demonstrated that gaseous CO 2 dissolved in melts exists as CO 2 and CO 3 2-, and it is generally agreed 30,31,[35][36][37][38][39][99][100][101][102] that the overall stoichiometric reaction for CO 2 uptake is…”
Section: Kinetic and Thermodynamic Aspects Of Gas Dissolution In Meltsmentioning
confidence: 99%
“…Raman analysis, Figure , was used to understand the bond and structure changes caused by SO 3 additions. It has been shown that, under oxidizing conditions, silicate and borosilicate glasses with sulfur additions will exhibit a large S 6+ –O symmetric stretching mode from 990 to 1000/cm . This peak was clearly seen, and the intensity of the peak grew with increasing sulfur loading.…”
Section: Resultsmentioning
confidence: 98%
“…In particular, the coordination of the oxygen and ratio of bridging (O 0 ), non‐bridging (O − ), and free oxygen (O 2− ) in the melt system will affect incorporation. Sulfur reduction‐oxidation state (redox) thus plays an important role in determining solubility and structure in the glass . The sulfur species incorporated into the glass is usually described as isolated sulfate units, typically surrounded by network‐modifying cations such as sodium .…”
Section: Introductionmentioning
confidence: 99%